2019
DOI: 10.18203/2320-6012.ijrms20190933
|View full text |Cite
|
Sign up to set email alerts
|

What should be the PSA threshold value? 2.5 or 4 ng/mL?

Abstract: Background: In this study, author aimed to detect of threshold value of prostate-specific antigen (PSA) to distinguish malignant or benign prostatic lesions in PSA evaluation.Methods: A total of 61 patients underwent TRUSBP due to high PSA values (2.5-4 ng/mL) at the clinic between 2012-2017. Digital rectal examinations of all patients were normal. Cases with PSA elevation were divided into groups according to the pathology by benign (group 1) or malign (group 2). Author evaluated the predictive factors with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In most studies that included SUVmax values in PI, the malignant group's average SUVmax values were higher than in the benign group [6,8,10,11,12,13,14,19]. The difference was not statistically significant [17,20,21,22,23,24], except for a few studies [8,14]. Yang et al stated that the SUVmax values of the malignant group were higher than in the benign group, and the difference was statistically significant (p < 0.01), but they reported that there was considerable overlap between the two groups, as in other studies [14].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In most studies that included SUVmax values in PI, the malignant group's average SUVmax values were higher than in the benign group [6,8,10,11,12,13,14,19]. The difference was not statistically significant [17,20,21,22,23,24], except for a few studies [8,14]. Yang et al stated that the SUVmax values of the malignant group were higher than in the benign group, and the difference was statistically significant (p < 0.01), but they reported that there was considerable overlap between the two groups, as in other studies [14].…”
Section: Discussionmentioning
confidence: 94%
“…These statistical differences compared with other studies were considered to be due to the use of more selective criteria in determining the benign group. While creating the benign group in our study, a lower cutoff value of 2.5 was used for PSA, taking into account recent publications [20,22]. Also, because 18F-FDG PET/CT is a preferred examination in the follow-up of oncology patients in our hospital, it was possible to examine the changes of PIs in previous and subsequent PET/CTs.…”
Section: Discussionmentioning
confidence: 99%